Pembuatan Green Inhibitor Dari Ekstrak Kopi Dengan Menggunakan Metode Sokletasi Pada Baja Karbon - Abdul Rahman Marwis Karim; Komalasari Komalasari (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
Corrosion is a degradation of metals quality caused by chemical reaction between metal and its ambient. The used of green inhibitor is a natural methods to control the corrosion rate of metal. The objective of this research is to count the efficiency of green inhibitor from coffee extract, to find which variable that affect the most of corrosion rate of mild steel, to determine the best concentration of extracts to control the corrosion rate of mild steel. The extraction methods is Soxhletation with solvent rasio 1 : 4 of ethanol : aquadest. Weight loss method is used to determine the rate of corrosion with 0,5;1;1,5 g/l variance of inhibitor concentrations and 3, 6, 9, 12 days contact times. The lowest corrosion rate is 150,22 mpy at 1,5 g/l of coffee extract inhibitor solution with 9 days contact times and the highest efficiency is 51,44% at 1,5 g/l of coffee extract inhibitor solution with 12 days of contact times.Keywords: coffee extract, green inhibitor, soxhletation,